Antimicrobial and Anti-Inflammatory Activity of Apple Polyphenol Phloretin on Respiratory Pathogens Associated With Chronic Obstructive Pulmonary Disease - Birru, Rahel L.; Bein, Kiflai; Bondarchuk, Natalya; Wells, Heather; Lin, Qiao; Di, Y. Peter; Leikauf, George D. (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial infections contribute to accelerated progression and severity of chronic obstructive pulmonary disease (COPD). Apples have been associated with reduced symptoms of COPD and disease development due to their polyphenolic content. We examined if phloretin, an apple polyphenol, could inhibit bacterial growth and inflammation induced by the main pathogens associated with COPD. Phloretin displayed bacteriostatic and anti-biofilm activity against nontypeable Haemophilus influenzae (NTHi), Moraxella catarrhalis, Streptococcus pneumoniae, and to a lesser extent, Pseudomonas aeruginosa. In vitro, phloretin inhibited NTHi adherence to NCI-H292 cells, a respiratory epithelial cell line. Phloretin also exhibited anti-inflammatory activity in COPD pathogen-induced RAW 264.7 macrophages and human bronchial epithelial cells derived from normal and COPD diseased lungs. In mice, NTHi bacterial load and chemokine (C-X-C motif) ligand 1 (CXCL1), a neutrophil chemoattractant, was attenuated by a diet supplemented with phloretin. Our data suggests that phloretin is a promising antimicrobial and anti-inflammatory nutraceutical for reducing bacterial-induced injury in COPD.